A (docência)lescência: pressupostos para um ensino Desenvolvimental - Souza, Cláudia Silva de (2016)
Adolescence has been focused, under the point of view of traditional Psychology, as a natural and universal phase of human development, which considers the subject on na individualizing perspective. Such understanding brings out repercussions not only to the understanding about adolescence but to the practices driven to this public, notedly the pedagogical one. In this sense, one has searched support on the Historical-Cultural Approach, a theoreticalmethodological foundation which tries to understand dialetically the relationships between the individual and the society, highlighting the historical dimension of its constitution, to do this thesis. Thus, the general objective of such research is to investigate the teacher´s understanding of adolescents on the psychological characteristics of his students and how it influences his pedagogical practice. One has had as specific objectives the building of a psychological characterization of adolescence; the identification and analysis of teacher´s understanding about the psychological characteristics of adolescence and the pedagogical practices developed from such understanding. Through a qualitative approach of research, the methodological procedures used to apprehend the reality investigated were questionnaires followed semi addressed interviews with nine teachers of adolescents from a federal state school of Minas Gerais. The analysis pinpoint the teacher´s understanding as a significant aspect in the development of the adolescent´s personality. One has identified that such understanding does not require from the teacher only general knowledge about adolescence as an evolutionary phase, but also the observation of singularity of each student. Another important aspect is the teacher´s positioning before such understanding, that is, his pedagogical practice which, by its turn, is inserted on the school context of a certain society. One has identified that adolescence is a phase of human development which, as any other, has characteristics, peculiarities, psychological tendencies and regularities, constituted from concrete conditions under which subjects live. However, the social situation of the development is a central category to understand all the transformations which take place at this phase, for it is related to the great restructuration which takes place in the relationships between the subject and his environment, through changes that present, above all, a qualitative character, resulting in new formations of personality. Among the several dimensions which constitute the social situation of the development, the relationships between student and teacher have had a highlight in this study, once the understanding of teachers about adolescent´s characteristics was, predominantly, related to such aspect. The teacher faces, in the school daily routine, students which demand ways of acting too much peculiar to the phase they live, demanding form him such knowledge and abilities which surpass the domain of contents and point to the importance to know how to conduct the personal relationships, considering the psychological characteristics of such public. In this sense, it is fundamental the organization fo the colective of the classroom, having in mind the impacts of such on the sutdent´s personality, whose intensive formation process of personal identity makes him extremely sensitive to social opinions. One hope that such systematizations done in the present study contribute to the production of theoretical subsidies about the relationships between teaching and adolescent´s development, in the Historical-Cultural approach. This work presents as a group of information which may configure into assumptions to the constitution of a Developmental Teaching, turned to adolescence. Such assumptions may even become source of studies and of other researches, as well as constitute of contents for pre service teaching and post graduation for teachers of elementar school.